Evaluation of bone marrow reconversion in healthy adults with knee MRI - Akgün, Ayşe Serap (Dicle University, 2020)
Objective: Radiologists encounter bone marrow reconversion (BMR) frequently when evaluating knee magnetic resonance imaging (MRI). It is clinically important to know what these changes may be related to. The aim of this study to investigate the relationships between BMR at MRI with age, gender, body mass index (BMI), smoking and hemoglobin (hgb) levels in healthy adults. Methods: In this prospective study, 107 healthy adults aged 26-62 years (55 women, 52 men ) were evaluated with knee MRI. The participants were divided according to the smoking histories as two groups: nonsmokers and heavy smokers. Red bone marrow changes examined by a radiologist in coronal T1-weighted sequences and classified into four groups according to their sizes. The levels of blood hgb of all patients were acquired and BMIs’ were calculated. Statistical analyzes were performed with the SPSS 17.0 program. Results: 24 (54.55%) of 44 patients with BMR were nonsmokers and 20 (45.45%) were heavy smokers. No statistically relation was found between marrow BMR and smoking history (p>0,05). BMR was found to be more prevalent in obese female patients and over 41 years old patients (p<0,001). A statistically significant relationship between the grades of BMR and hgb values was detected (p=0.013). Conclusions: Whereas BMR is irrelevant with smoking, it is common especially in middle aged obese women. A significant relationship was found between the hgb values and the grades of BMR. These parameters should be kept in mind when BMR seen in MRI and these patients should be directed to laboratory assessment for anemia.

Amaç: Radyologlar, diz manyetik rezonans görüntüleme (MRG) bulgularını değerlendirirken sıklıkla kemik iliği rekonversiyonu (KİR) ile karşılaşırlar. Bu değişikliklerin nelerle ilgili olabileceğini bilmek klinik olarak önemlidir. Bu çalışmanın amacı, sağlıklı erişkinlerde MRG’de KİR ile yaş, cinsiyet, vücut kitle indeksi (VKİ), sigara ve hemoglobin (hgb)düzeyleri arasındaki ilişkileri araştırmaktır. Yöntemler: Bu prospektif çalışmada yaşları 26 ile 62 arasında değişen toplam 107 sağlıklı erişkin (55 kadın, 52 erkek)diz MRG ile değerlendirildi. Hastalar, sigara öykülerine göre sigara içmeyenler ve ağır içiciler olarak iki gruba ayrıldı. Kırmızı kemik iliği değişiklikleri radyolog tarafından T1 A koronal sekanslarda değerlendirildi ve boyutlarına göre 4grupta sınıflandırıldı. Tüm hastaların eş zamanlı kan hgb seviyeleri ölçüldü ve VKİ’leri hesaplandı. İstatistiksel analizler SPSS 17.0 programı ile yapıldı.Bulgular: Rekonversiyon görülen 44 hastanın 24’ü (%54,55) sigara içmeyen, 20’si (%45,45) ağır içicidir. Rekonversiyon ve sigara kullanımı arasında anlamlı ilişki bulunamadı (p>0,05). Rekonversiyon, obez kadınlarda ve 41 yaş üzeri hastalarda istatiksel anlamlı olarak daha çok saptandı (p<0,001). Rekonversiyonun derecesi arttıkça hgb değerlerinin anlamlı olarak düştüğü gözlendi (p=0.013).Sonuç: KİR, sigara ile ilişkisiz olup orta yaş ve üzeri obez kadın hastalarda daha sık görülmektedir. Hgb değerleri ile KİRgradeleri arasında önemli ilişki görülmüştür. MRG’lerinde KİR saptanan hastalarda bu parametreler akılda tutulmalı ve bu hastalar anemi için laboratuvar değerlendirmesine yönlendirilmelidir.
Kemik iliği rekonversiyonunun sağlıklı erişkinlerde diz MRG ile değerlendirilmesi
Keywords: Bone and Bones; Bone Marrow; Tobacco Products; MRI; Kemik ve Kemikler; Kemik İliği; Tütün Ürünleri; MRG